Literature Review: PENGARUH RESISTANCE EXERCISE DENGAN ELASTIC BAND UNTUK EKSTREMITAS BAWAH TERHADAP WALKING SPEED PADA LANJUT USIA - Annisa Indahtyas Mussalam Setiawan (2020)
[Purpose] The purpose of this study is to determine whether there is an influence of Resistance Exercise with Elastic Band for lower extremities on walking speed in the elderly, so as to minimize the risk of falling in the elderly. [Subject and Method] Elderly patients with a generally healthy physique and can walk without assistance. This research uses the Literature Study method. [Results] From the findings of 6 journals sourced from Google Schoolar, Pubmed, Scient Direct, and Jospt that Resistance Exercise uses Elastic Bands for lower limbs for Walking Speed in the elderly there is a significant change in the duration of walking, on the other hand in the Saeterbakken et al study ., 2018 there were no significant changes in the duration of the walk. [Conclusion] From 6 studies, the Walking Speed Test using Resistance Exercise using intervention (Elastic Band) with different parameters, concluded that the walking speed using the 4.44 Meter Walk parameter and the Fried Frailty Phenotype is better used compared to the Minnesota Living with Heart Failure Questionnaire ( MLHFQ) and Time Up and Go Test (TUG).